Use of density functional theory for modeling optical properties of vacancy defects in nanoclusters of various SiC polytypes - Zhikol, O.A.; Luzanov, A.V.; Omelchenko, I.V.; Pushkarchuk, A.L.; Pushkarchuk, V.A.; Nizovstev, A.P.; Kilin, S.Ya.; Bezyazychnaya, T.V.; Kuten', S.A. (Functional Materials, 2018)
We studied electronic properties of the ground and lowest excited states of SiC defective nanoclusters falling into 3C, 2H and 4H polymorphic types. The standard time-dependent DFT method was used along with the economical model-core-potential approximation. Basing on our earlier works, we performed the corresponding excited state structural analysis and show for the lowest triplet-triplet ransition a significant effect of excitation localization in the defect vicinity.